2011
DOI: 10.1111/j.1478-3231.2011.02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Different sites of xenoantigen delivery lead to a virally induced late‐onset hepatitis in mice through molecular mimicry

Abstract: Liver autoimmune response can be initiated using molecular mimicry over a long period of time, validating the hit-and-run hypothesis. Initial liver inflammatory injury is neither necessary, nor detrimental to the development of AIH. These results highlight the significance of initial events on the pathogenesis of autoimmune liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Other authors suggested that peripheral T lymphocytes could play a role in hepatic immune responses, and the hypotheses include T lymphocyte competition for antigen presentation in hepatic or peripheral lymphoid tissues, 10 late T cell activation in the liver after peripheral antigen priming, 11 peripheral IL‐12‐dependent reversion of liver‐induced immune tolerance, 12 and others 13,14 . The experimental models include AIH induced in transgenic mice and expression of hepatitis viral antigens; although we believe that part of these results further supports our model, experimental limitations impaired the unequivocal interpretation of those previous data.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Other authors suggested that peripheral T lymphocytes could play a role in hepatic immune responses, and the hypotheses include T lymphocyte competition for antigen presentation in hepatic or peripheral lymphoid tissues, 10 late T cell activation in the liver after peripheral antigen priming, 11 peripheral IL‐12‐dependent reversion of liver‐induced immune tolerance, 12 and others 13,14 . The experimental models include AIH induced in transgenic mice and expression of hepatitis viral antigens; although we believe that part of these results further supports our model, experimental limitations impaired the unequivocal interpretation of those previous data.…”
Section: Discussionsupporting
confidence: 69%
“…Zeng et al 12 . showed that an IL‐12‐based vaccination therapy reversed immune tolerance in the liver, and other authors investigated the importance of the site of antigen expression in hepatic tolerance 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have proven that a short, self-limiting liver-specific infection can cause chronic evolving emAIH in animals on NOD background that are prone to the development of autoimmunity [2]. The lack of viral infection during the chronic phase of disease supported a hit-and-run hypothesis for the development of AIH in which an initial stimulus was sufficient to trigger autoimmunity [34].…”
Section: Discussionmentioning
confidence: 76%
“…It was also proposed that antigen-primed T lymphocytes migrate from the lymph nodes and are retained in the liver for activation when in the presence of a more pro-inflammatory environment, in the case of second antigen exposure [ 144 ]. Other authors showed that an IL-12-based vaccine reversed immune tolerance in the liver [ 145 ], and other papers showed the importance of the anatomical site of antigen expression in hepatic tolerance [ 146 , 147 ]. However, in all experimental approaches used, the possibility of antigen presentation in both lymph nodes and the liver could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%